Pochodzenie funkcji estetycznej języka = The emergence of the esthetical function of the language - Kotin, Michail L. (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The esthetical function of human languages is, beside the cognitive, communicative and expressive functions, commonly considered as one of their basic functions. However, the origin of the esthetical function is controversial as well. From the perspective of the language genealogy, it seems to be rather a secondary function, but if we accept this, the question still remains, what primary function it was derived from.
Keywords: funkcja estetyczna języka; adaptacja; egzaptacja; zmiany językowe; esthetical function of the language; adaptation; exaptation; language change